2017
DOI: 10.3171/2017.3.focus1751
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of blister aneurysms

Abstract: Blister aneurysms are rare cerebrovascular lesions for which the treatment methods are reviewed here, with a focus on endovascular options. The reported pathogenesis of blister aneurysms varies, and hemodynamic stress, arterial dissection, and arteriosclerotic ulceration have all been described. There is consensus on the excessive fragility of blister aneurysms and their parent vessels, which makes clipping technically difficult. Open surgical treatment is associated with high rates of complications, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 54 publications
0
34
0
Order By: Relevance
“…Later, these patients were treated with flow-diverting stents without additional coil placement [10, 11]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, these patients were treated with flow-diverting stents without additional coil placement [10, 11]. …”
Section: Discussionmentioning
confidence: 99%
“…Patients with blister aneurysms were treated with single or double stenting at the start of the study period, using conventional stents [ 9 ]. Later, these patients were treated with flow-diverting stents without additional coil placement [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blister aneurysms are rare vascular lesions. The most common localization of these aneurysms is supraclinoid with a proportion of 0.3%–1.7% of all aneurysms and up to 6.6% of aneurysmal ruptures [ 9 ]. Blister aneurysms have a higher risk of complications, such as rebleeding or even mortality [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Unruptured DAs are associated with stroke due to significant arterial stenosis, occlusion or pseudoaneurysm formation with subsequent haemodynamic and embolic infarcts or complications from mass effect; moreover, BAs and DAs are prone to rupture. 2,12 Open surgical techniques carry a high risk of morbidity and mortality, predominantly due to intraoperative rupture due to the fragility of the parent vessel wall. 7,8,13 In particular, the fusiform morphology in DAs and lack of a defined neck in BAs makes conventional endovascular techniques and surgical clipping impossible or inadequate in many cases.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] The reason why treatment of acutely ruptured BAs and DAs even with stents as monotherapy is effective can be explained by the findings of experimental studies that have demonstrated haemodynamic changes by stents. 12,20 Stents induce decrease of wall shear stress, inflow momentum, velocity and vorticity, and this might prevent aneurysmal rupture. Increased intraaneurysmal blood turnover time by diverting blood flow from the aneurysm and by dispersing the inflow into the aneurysm might promote thrombosis.…”
Section: Discussionmentioning
confidence: 99%